Effect of Repeated Cyclic Lateral Loads on Load Bearing Shear Wall Panels - de Lisle, D. J. (My University, 1971)
The slitted wall, a concept originally used to improve the properties of infilled wall panels, is applied to shear wall structures. An ordinary reinforced concrete wall and three slitted walls were tested under cycles of repeated lateral displacements. The effect of vertical load and the lengthening of the slits to full panel height was also investigated.
The walls are compared by considering the different crack formations, stiffness deteriorations, load-deflection characteristics and energy properties. It is shown that vertical slits do not produce improvements to the lateral response of wall panels. The application of vertical loads is beneficial and the lengthening of the vertical slits to full panel height is detrimental to the behaviour of the wall panels.
Keywords: civil engineering; repeated, cyclic lateral loads; load bearing; shear wall, panel